Potensi Likuifaksi Pada Tanah Timbunan Pasir Di Atas Tanah Gambut Dengan Variasi Berat Beban Melalui Uji Model Laboratorium - Oki Chandra; Agus Ika Putra; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Five major earthquakes with magnitudes of more than 8 have affected Sumatra island 250 years ago (Natawidjaja, 2007). Riau province in the middle of Sumatra island is quite prone to get the impact of earthquake. The propagation of these earthquake waves causes geotechnical problems such as liquefaction. Liquefaction research has been done but the liquefaction potential in sand embankment on peat soil has never been done. The peatland in Riau Province is 3.9 million hectares out of 8.7 million hectares of Riau. So that many buildings in the Riau Province is above the peat land bankfilled with sand. This study uses a laboratory model of shaking table with speeds of 0.25 g and 0.32 g. A 0.5x1.0 meter acrylic box is installed on a shaking table and filled with 10 cm thick peat soil, then banckfilled it with 15 cm thick of sand. The peat soil and sand embankment are saturated, then the load is evenly distributed with variations of 40 kg/m2, 80 kg/m2, and 120 kg/m2. Evaluation of liquefaction potential is based on observation of the increment of pore water pressure measured by installing two vertically bankfilled pipe with a depth of 7.5 cm. On the sides of the acrylic box is also installed two rulers to observe the soil settlement. The results of this study indicate that as the given load increased, soil settlement and increase of pore water also increased. The weight of the load is also directly proportional with soil vertical pressure and pore water pressure ratio value.Keywords: liquefaction,sand, peat soil, pore water pressure, shaking table